Global land cover uncovered - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
In order to fully understand how land is being used for food production and foresee how land use will change in the future, reliable crop maps are essential. Not only can crop maps help identify yield gaps and monitor crops affected by drought, they can also help tackle environmental issues. As agricultural expansion is a major cause of deforestation, knowing where new crops are grown could assist calculations of additional greenhouse gas emissions, useful for initiatives to reduce emissions from deforestation, or determining the implications of climate change on crop production. But at present, there is no single global land cover product available that accurately displays where crops are grown. Some land cover maps even disagree over vast areas of the Earth’s surface. With the ambition to improve the quality of global land cover maps, a team based at the International Institute for Applied Systems Analysis (IIASA) started the pioneering Geo- Wiki project, a geospatial Wikipedia that uses the growing body of satellite imagery, Google Earth as a platform and crowdsourcing as the mechanism for collecting and verifying data.